PELATIHAN MANAJEMEN ASET DESA DI DESA MEREMPAN HULU KECAMATAN SIAK, KABUPATEN SIAK - Yunieta Anisma; Yusralaini; Susilatri; Taufeni Taufik (LPPM UMRI, 2019)
Abstract Every teaching institution has a tri dharma that must be carried out by its lecturer. One form of tri dharma tertiary education is community service. Community service is carried out so that lecturers use science and technology to advance the welfare of society and educate the nation's life. The form of dedication carried out was village asset management training in Merempan Hulu Village, Siak Subdistrict, Siak District, with 30 participants coming from the villages of Buantan Besar, Langkai, and Merempan Hulu. Participants consisted of the village head, elements of the village apparatus involving KKN students in Merempan Hulu. With the aim of the activity, participants understand the meaning of village asset management, the scope and principles of village asset management. After this training is expected the village head and village apparatus will understand village asset management and village asset management. In this training more than 80% of participants understood the training on asset management and village asset management. Keywords: Training, Village Asset Management, Merempan Hulu Village, Siak District Abstrak Setiap penguruan tinggi memiliki tri dharma yang harus dijalankan oleh dosennya. Salah satu bentuk tri dharma perguruan tinggi adalah pengabdian kepada masyarakat. Pengabdian kepada masyarakat dilakukan agar pada dosen memanfaatkan ilmu pengetahuan dan teknologi untuk memajukan kesejahteraan masyarakat dan mencerdaskan kehidupan bangsa. Adapun bentuk pengabdian yang dilakukan adalah pelatihan manajemen aset desa di Desa Merempan Hulu Kecamatan Siak, Kabupaten Siak, dengan jumlah peserta 30 orang yang berasal dari desa Buantan Besar, Langkai, dan Merempan Hulu. Peserta terdiri dari kepala desa, unsur perangkat desa dengan melibatkan mahasiswa KKN di Merempan Hulu. Dengan tujuan kegiatan, peserta memahami makna manajemen aset desa, lingkup dan prinsip-prinsip pengelolaan aset desa. setelah dilakukan pelatihan ini diharapkan kepala desa dan perangkat desa memahami manajemen aset desa dan pengelolaan aset desa. Dalam pelatihan ini lebih dari 80 % peserta memahami pelatihan manajement aset dan pengelolaan aset desa. Kata kuncis: Pelatihan, Manajemen Aset Desa, Desa Merempan Hulu, Kecamatan Siak